The impact of the green Middle East initiative on sustainable development in the Kingdom of Saudi Arabia - Adel M. Ghanem; Yosef A. Alamri (Journal of the Saudi Society of Agricultural Sciences)
Using econometric analysis, this study intended to determine the influence of the Green Middle East Initiative on sustainable development in the Kingdom of Saudi Arabia from 2000 to 2020. This research yielded a number of findings, the most important of which are: The country has tended to reduce carbon emissions by increasing natural gas use and decreasing diesel and crude oil use in electricity generation. The real per capita income increased by 0.8 percent annually due to the unpredictability and instability of the economic growth rate. The Human Development Index has similarly risen, from 0.744 in 2000 to 0.855 in 2020. It was also discovered that a 10% increase in domestic refined petroleum product consumption results in a 7.97% rise in carbon dioxide emissions. And that a 10% rise in predicted carbon dioxide emissions results in 4.71 percent, 0.36 percent, and 0.71 percent decreases in foreign direct investment, real GDP, and the value of the human development index, respectively. And the Green Middle East initiative included planting 10 billion trees irrigated with untapped treated sewage water amounting to 1528.49 million m3, with a value of 2.094 billion riyals. Finally, the gradual transformation of the green economy leads to environmental sustainability and integration between the environment, economic, and social dimensions of sustainable development, and then this study recommends the necessity of following up and evaluating the results of the work of the Green Middle East Initiative so that carbon emissions eliminated in the Kingdom of Saudi Arabia until 2060.